Oral and Topical Administration of a Standardized Saw Palmetto Oil Reduces Hair Fall and Improves the Hair Growth in Androgenetic Alopecia Subjects – A 16-Week Randomized, Placebo-Controlled Study - Sudeep HV; Rashmi S; Jestin TV; Richards A; Gouthamchandra K; Shyamprasad K (Dove Medical Press, 2023)
Heggar Venkataramana Sudeep,1 Sriram Rashmi,2 Thomas V Jestin,3 Aleksander Richards,4 Kuluvar Gouthamchandra,1 Kodimule Shyamprasad1 1Department of Biomedicinal Research, R&D Center for Excellence, Vidya Herbs Pvt Ltd, Bangalore, Karnataka, India; 2BGS Global Institute of Medical Sciences, Bangalore, Karnataka, India; 3Department of Clinical Research, Leads Clinical Research and Bio Services Private Ltd, Bangalore, Karnataka, India; 4Department of Clinical Studies, R&D, Vidya Herbs, Red Bank New Jersey USACorrespondence: Heggar Venkataramana Sudeep, Department of Biomedicinal Research, R&D Center for Excellence, Vidya Herbs Pvt Ltd, Bangalore, Karnataka, India, Email research@vidyaherbs.com; sudeepkashyap.82@gmail.comPurpose: Androgenetic alopecia (AGA) is the most common type of hair loss in humans, affecting self-esteem and emotional well-being. This study aimed to assess the safety and efficacy of VISPOTM, a standardized saw palmetto oil (2- 3% β-sitosterol), in subjects with mild-to-moderate AGA.Methods: In a double-blind, placebo-controlled, four-arm clinical study, 80 healthy male and female subjects aged 18- 50 years were randomly allocated (1:1:1:1) to receive either 400 mg capsules of VISPO or 5 mL of a topical formulation containing 20% VISPO or the respective placebo once daily for 16 weeks. The primary endpoints included hair count (hair comb and hair pull tests) and the self-assessment of perceived efficacy. Objective evaluation was performed using the global photographic assessment score. Hair density, thickness, and anagen/telogen ratio were evaluated using phototrichogram analysis.Results: At the end of the study, oral and topical formulations of VISPO reduced hair fall by up to 29% (p< 0.001) and 22.19% (p< 0.01) from the baseline, respectively. Hair density increased by 5.17% and 7.61% in the oral and topical VISPO groups, respectively (p< 0.001). In addition, oral ingestion of VISPO resulted in a marked reduction in serum dihydrotestosterone (DHT) levels in the subjects compared to placebo (p< 0.001). However, the effect of the VISPO formulations on the anagen/telogen ratio was insignificant. No serious adverse effects were observed during the study.Conclusion: VISPO formulations reduced hair fall and promoted hair regrowth and scalp appearance in AGA patients.Keywords: hair loss, androgenetic alopecia, saw palmetto, β-sitosterol, fatty acids